Airway Management in a Patient with Wolf-Hirschhorn Syndrome - John F. Gamble; Dinesh J. Kurian; Andrea G. Udani; Nathaniel H. Greene (Case Reports in Pediatrics)
We present a case of a 3-month-old female with Wolf-Hirschhorn syndrome (WHS) undergoing general anesthesia for laparoscopic gastrostomy tube placement with a focus on airway management. WHS is a rare 4p microdeletion syndrome resulting in multiple congenital abnormalities, including craniofacial deformities. Microcephaly, micrognathia, and glossoptosis are common features in WHS patients and risk factors for a pediatric airway that is potentially difficult to intubate. We discuss anesthesia strategies for airway preparation and management in a WHS patient requiring general anesthesia with endotracheal intubation.